A Retrospective Study on the Clinical Safety of Bee Venom Pharmacopuncture at Craniofacial Acupuncture Points for the Treatment of Facial Disorders - Chang Hee Lee; Jin-Young Yoon; Sung-Eun Shim; Jeong Hyun Kim; Jun-Yeon Kim; Ha-Na Kim; Ji-Min Hwang; Jung-Hyun Kim; Bon Hyuk Goo; Yeon-Cheol Park; Byung-Kwan Seo; Yong-Hyeon Baek; et al. (MEDrang Inc., 2019)
Background This study was designed to evaluate the clinical safety of Bee Venom (BV) pharmacopuncture at craniofacial acupuncture points. Methods This was a retrospective study of 108 patients diagnosed with peripheral facial paralysis, trigeminal neuralgia, or facial spasm who were admitted to Kyung Hee University Korean Medicine Hospital at Gangdong, from April 1st, 2017 to August 30th, 2017. Patients were allocated into either, Group 1 (the non-allergy group of patients who did not have an allergic reaction to BV) or Group 2, the group who had allergic reactions to BV. To evaluate the clinical safety of BV pharmacopuncture after each treatment, several criteria were used to measure any side effects: outcome, Common Terminology Criteria for Adverse Events scale, Mueller HL scale, treatment decision after adverse reaction, causality, measures performed for patients with adverse reactions, and efficacy assessment. Results BV pharmacopuncture delivered in 0.1-0.2 mL at a concentration of 1:30,000 at the craniofacial acupuncture points, showed no statistically significant differences in baseline characteristics between non-allergy Group 1 and allergy Group 2. Amongst the 108 patients, 11 reported side effects after BV pharmacopuncture treatment. These adverse events included rash (n = 7), pruritus (n = 5), swelling (n = 1), vesicles (n = 1), erythema (n = 1), and hives (n = 1). All side effects resolved without sequelae. Conclusions In this study, BV pharmacopuncture delivered at low doses at the craniofacial acupuncture points, resulted in 10% of patients experiencing non serious side effects suggesting that BV pharmacopuncture was clinically well tolerated.